Use of the Gespräch Mini Card Game as an Interactive Learning Media to Train German Speaking Skills in Class XI at UM Laboratory High School - Ningrum, R. Pertiwi Fajar; Kurniawan, Deddy (Universitas Negeri Malang, 2024)
This research aims to describe the activity of using the Mini Gespräch card game as an interactive learning medium to practice German speaking skills in class. The research method used by researchers is qualitative description. The data sources in this research were 21 high school students in class. The research results showed that German language learning activities using the interactive learning media Mini Gespräch game cards went well. The card game media can be used easily when learning takes place. Students can also continue to search for more new vocabulary on the internet and study Redemittel in the form of question sheets that have been provided flexibly. Apart from that, the Mini Gespräch card game media also makes them more enthusiastic about learning and not boring because of the attractive image display.